Influence of Sparshanam, a Medical Humanities Module on Personal and Professional Development among the First Batch of Medical Graduates in Lalitpur, Nepal: A Cross-Sectional Study - Shankar, Pathiyil Ravi; Dhakal, Ajaya Kumar; Piryani, Rano M; Shrestha, Devendra; Dwa, Yam Prasad (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Medical humanities (MH) uses subjects like literature, music, drama, and painting for specific purposes in medical education. We aimed to assess its medium-term impact on medical alumni whose curriculum incorporated a module on MH which was named as Sparshanam. Methods: After approval from the Institutional Review Committee of KIST Medical College, this cross-sectional online survey was performed from December 2020 to January 2021on the 2008 batch medical alumni who had experienced Sparshanam in their medical education curriculum 10 years before. A mixed modal design (both qualitative and quantitative) was applied. The participants’ perception of the module, like its strengths, weaknesses, and its contribution to personal and professional development were assessed. Results: Out of the 75 first batch alumni, 39 (52%) participated. Most of them were working in the Kathmandu valley. The perceived strengths were teamwork, interactive group sessions, and imparting a holistic perspective of patients. The Sparshanam was perceived to enhance their teamwork, communication, leadership and clinical observation skills, and ability to empathize with patients. Participants perceived it to have an important influence on their development and recommended its introduction in the undergraduate and postgraduate clinical training. Conclusion: The Sparshanam was perceived to have a significant impact on their personal and professional development.